Envolvimento das espécies reativas de oxigênio e das citocinas na hipertensão - Lauar, Mariana Ruiz (Universidade Federal de São Carlos, 2017)
Arterial hypertension (AH) is a multifactorial disease, characterized by increased levels of arterial pressure (AP) that causes an increased risk of coronary disease, stroke and congestive heart failure. Several studies have addressed the possible causes and mechanisms of hypertension in the attempt to seek new treatments for this disease. Studies have already showed the participation of oxidative stress, caused by increased production of reactive oxygen species (ROS) in the development and maintenance of hypertension. ROS like hydrogen peroxide (H2O2) are produced endogenously and may participate in intra- and extracellular signaling, including mediation of angiotensin II (ANG II) responses. Intracerebroventricular injection of H2O2 or the increase of endogenous H2O2 using the catalase inhibitor ATZ reduced the pressor responses to central ANG II in normotensive and hypertensive rats. In the present study, we investigated the effects of acute or chronic subcutaneous (sc) administration of ATZ on mean arterial pressure (MAP) and heart rate (HR) in normotensives, spontaneously hypertensive rats (SHR) and 2-kidney, 1clip hypertensive rats (2K1C). We also studied the possible changes of autonomic modulation of systolic arterial pressure (SAP) and the pulse interval (PI), the renal sympathetic nerve activity, the baroreflex, the genic expression of inflammatory cytokines, components of the renin-angiotensin system (RAS), NADPH oxidase isoforms and microglia activity (CD11) in the hypothalamus in rats treated with sc ATZ. In addition, it was also tested the pressor response to noradrenaline or ANG II injected intravenously (iv), the hypotensive response to the ganglionic blockade with hexamethonium, food and water intake and urinary excretion in normotensive and hypertensive rats treated with sc administration of ATZ. Male normotensive Holtzman, 2K1C hypertensive Holtzman rats and SHR were used. MAP and HR were recorded in conscious, unrestrained rats, except in rats used to record sympathetic activity. The sc injection of ATZ (300 mg/kg of body weight) acutely reduced MAP in SHR (192 ± 4 mmHg pre-injection of ATZ vs. 173 ± 6 mmHg after ATZ) and in 2K1C rats (170 ± 8 mmHg pre-injection of ATZ, vs. 158 ± 13 mmHg after ATZ) for at least 4 h and also slightly reduced HR. Chronic daily treatment with ATZ (600 mg/kg of body weight/day) sc for 9 days also reduced MAP in SHR (ATZ: 172 ± 8 mmHg, vs. saline: 198 ± 2 mmHg) and in 2K1C rats (ATZ: 137 ± 12 mmHg, vs. saline: 181 ± 9 mmHg) without altering HR, the impairment of baroreflex present in hypertensive rats, food and water intake and urinary excretion. The treatment with ATZ sc chronically reduced sympathetic modulation of SAP in SHR (ATZ: 2.6 ± 1.2 mmHg2, vs. saline: 6.3 ± 3.4 mmHg2) and in 2K1C rats (ATZ: 3.2 ± 0.4 mmHg2, vs. saline: 7.6 ± 1.5 mmHg2) and PI, enhanced the parasympathetic modulation of PI in SHR (ATZ: 90.5 ± 4.5 un, vs. saline: 76.5 ± 7.8 un) and 2K1C rats (ATZ: 85.3 ± 2.9 un vs. saline: 68.6 ± 3 un) and improved the sympatho-vagal balance in SHR (ATZ: 0.11 ± 0.05, vs. saline: 0.35 ± 0.17) and in 2K1C rats (ATZ: 0.19 ± 0.05, vs. saline: 0.52 ± 0.09). Chronic treatment with ATZ sc for 9 days in 2K1C hypertensive rats also reduced the mRNA expression of interleukin-6 (IL-6) (ATZ: 0.80 ± 0.06, vs. saline: 2.32 ± 0.36 fold change), tumor necrosis factor-α (TNF-α) and AT1 receptor (AT1r) (ATZ: 0.74 ± 0, 04, vs. saline: 1.19 ± 0.22 fold change) in the hypothalamus. ATZ chronically in SHR also decreased mRNA expression of IL-6 (ATZ: 1.17 ± 0.07, vs. saline: 1.53 ± 0.11 fold change), AT1r (ATZ: 0.81 ± 0.03, vs. saline: 1.0 ± 0.04 fold change), NADPH oxidase isoform NOX2 (ATZ: 0.85 ± 0.06, vs. saline: 1.52 ± 0.27 fold change) and the microglia activation indicator gene (CD11) (ATZ: 1.47 ± 0.06, vs. saline: 1.79 ± 0.08 fold change) in the hypothalamus. The injection of ATZ (300 mg/kg of body weight) sc in 2K1C hypertensive rats acutely reduced renal sympathetic nerve activity (-51.5 ± 10%) and the hypotensive response to iv injection of the ganglionic blocker hexamethonium (ATZ: -58 ± 5 mmHg; vs. saline: -106 ± 7 mmHg), without changing the pressor responses to noradrenaline or ANG II iv, in rats treated with sc ATZ. Therefore, the present results suggest that increasing the availability of endogenous H2O2 by the acute or chronic administration of ATZ sc produces anti-hypertensive effects due to decreases in sympathetic nerve activity that are associated with a decrease in neuroinflammation, AT1 receptor and NADPH oxidase mRNA and activation the microglia in the hypothalamus. These effects might result from an impairment of the central action of ANG II as demonstrated in a previous study (LAUAR et al., 2010).
Keywords: Hipertensão; Inibidor da catalase; Neuroinflamação; Hipotálamo; Hypertension; Catalase inhibitor; Neuroinflammation; Hypothalamus; CIENCIAS BIOLOGICAS::FISIOLOGIA